A morphological and molecular analysis reveals a new species in the genus Diorygma (Graphidaceae, Ostropales) from Zhejiang Province, China - Jiang, Shu-Hao; Xu, Yuan-Ke; Zhao, Xin; Jia, Ze-Feng (Phytotaxa, 2025)
A new species of the lichenized fungi genus Diorygma is described from China: Diorygma jingningense Shu H. Jiang & Z.F. Jia, collected from Zhejiang Province. It is characterized by a saxicolous and pseudocorticate thallus, erumpent lirellae with complete thalline margin, entire labia, uncarbonized excipulum, hyaline hymenium, small, submuriform, 3 × 0–1-septate ascospores and the presence of norstictic and connorstictic acids. The placement of this new species was confirmed by a molecular phylogenetic approach based on combined mtSSU and nuLSU sequences, and is compared in detail with other similar species in the genus.